PENGARUH PENGGUNAAN CHATBOT DI APLIKASI X @TANYARLTERHADAP MINAT FOLLOWERS UNTUK REPLY - Ayanda Zahwa Sekar Cendani; Ageng Rara Cindoswari (LPPM Universitas Putera Batam, 2025)
The rapid development of information technology has driven changes in how people interact on social media, including through the use of chatbots. The X @TanyaRL application is a platform that utilizes chatbots to efficiently deliver public service information. However, there are still limitations in the chatbot's ability to understand conversational context, as well as in the quality of the content, which has yet to fully meet user expectations. This has resulted in a low level of follower engagement in replying, highlighting the need for scientific research to understand the factors influencing digital engagement. This study aims to analyze the influence of chatbot usage and content quality on followers’ interest in replying on the X @TanyaRL application. Data was collected from followers through field surveys using a stratified random sampling method. Data analysis was conducted using both quantitative descriptive and qualitative approaches, with the help of SPSS version 26 and multiple linear regression. The results indicate that chatbot usage does not significantly affect followers’ interest (significance value 0.106 > 0.05), whereas content quality has a significant effect (significance value 0.004 < 0.05). Simultaneously, the two variables contribute 43.60% to followers’ interest in replying. Therefore, improving content quality has greater potential to enhance follower interaction compared to relying solely on chatbot functionality Keywords:Chatbot usage, content quality, follower interest, uses and gratification, theory of planned behavioral